EXTENT OF UTILIZATION OF ARTIFICIAL INTELLIGENCE TOOLS FOR TEACHING BUSINESS EDUCATION COURSES AMONG BUSINESS EDUCATORS IN TERTIARY INSTITUTIONS IN DELTA STATE, NIGERIA (NAU Journal of Technology and Vocational Education, 2026)
This study focused on the extent of utilization of artificial intelligence (AI) tools for teaching business education courses among business educators in tertiary institutions in Delta State, Nigeria. Three research questions guided the study and two null hypotheses were tested at the 0.05 level of significance. The study adopted a descriptive survey design. The population comprised 140 business educators in government-owned tertiary institutions offering Business Education programmes, and no sampling was conducted due to the manageable population size. Data were collected using a 30-item structured questionnaire validated by three experts, with reliability established through Cronbach’s Alpha, yielding coefficients of 0.90, 0.92, and 0.89 for the three clusters, and an overall reliability of 0.90. Frequency counts, percentages, mean and standard deviation were used to answer the research questions, while chi-square and t-test analyses tested the hypotheses. Findings indicated a mixed level of awareness of AI tools among business educators, with higher familiarity for widely used applications such as ChatGPT, Siri, and Google Assistant. Despite this awareness, AI tools were largely unavailable and not utilized for teaching business education courses. Additionally, no significant difference was found in the mean ratings of AI utilization based on institutional ownership. The study concluded that while educators demonstrate varying levels of awareness, actual integration of AI tools into teaching remains limited. It was recommended that tertiary institutions implement structured awareness and training programmes for educators and students to improve understanding and effective use of AI in business education instruction.
Keywords: Artificial Intelligence (AI); Business Education; AI Utilization; Tertiary Institutions; Educational Technology Integration